Formulasi dan uji aktivitas antibakteri sediaan salep daging daun lidah buaya (Aloe vera L.) terhadap bakteri Staphylococcus aureus pada penyembuhan luka bernanah - Dena, Mutia; Dalimunthe, Gabena Indrayani; Lubis, Minda Sari; Rahayu, Yayuk Putri (Journal of Pharmaceutical and Sciences, 2023)
Staphylococcus aureus is one of the bacteria that can cause infectious diseases of the skin, one of which is purulent wound disease. Aloe vera (Aloe vera L.) belongs to the family Asphodelaceae, which is a plant known to have antibacterial compounds. The study was conducted experimentally. The independent variable is the concentration of aloe vera leaf flesh, 20%, 30% and 40%. The concentration of aloe leaf meat ointment is 20%, 30%, and 40%. The dependent variables are the antibacterial activity of aloe vera leaf meat ointment preparations against staphylococcus aureus bacteria. The results of the antibacterial Zone of Inhibition (ZOI) value of aloe vera leaf meat against staphylococcus aureus of 8.1 mm (20% concentration); 8.5 mm (concentration 30%); and 10.5 mm (concentration 40%). Antibacterial ZOI value of aloe leaf meat ointment against staphylococcus aureus by 10.6 mm (F1 20%), 11.5 mm (F2 30%), and 12.5 mm (F3 40%). The test results on purulent wounds in rat test animals get moderate healing scores on F1, F2, F3 and K + (gentamicin sulfate 0.1%) strong, so it can be said that aloe vera leaf meat ointment preparations can inhibit antibacterial growth in purulent wound healing even with a moderate category compared to Gentamicin ointment 0.1% with a strong (sensitive) category.